Pengaruh Kompetensi Sumber Daya Manusia, Sistem Pengendalian Intern, dan Penerapan Standar Akuntansi Pemerintahan Terhadap Kualitas Laporan Keuangan Pemerintah Daerah(Studi Empiris Pada SKPD Kota Surakarta) - Nugraheta, Ulfa Rima, Drs. Muhammad Abdul Aris, M.Si (2017)
The purpose of this study was to determine the effect of human resource competenc, internal control system, and the implementation of government accounting standards on the Quality of Local Government Financial Report (LKPD) in SKPD of Surakarta City.The population of this research is all staff in SKPDs of Surakarta City, using of questionnaires in data collection. Data collection is done by giving as many as 115 copies of the questionnaires which was distributed to all staff on expenditure treasurer and financial statements staff. The data obtained are then analyzed using SPSS 21.00.Based of the analysis result, obtained that the human resource competency has unsignificant effect on the Quality of Local Government Financial Report (LKPD) in SKPDs of Surakarta City, internal control system and the the implementation of government accounting standards on the Quality of Local Government Financial Report (LKPD) in SKPDs of Surakarta City.